Ethics of Buying and Selling in The Muslim Community, Case Study in The Traditional Manado Market - Riton Igisani (Tasharruf: Journal Economics and Business of Islam, 2019)
Abstract               This research discusses the ethics of buying and selling in the muslim community, especially in the traditional manado market, the subject of the discussion is on buying and selling ethical values using the approach of religious social phenomena.               For most of the manado muslim community, trading is a  profession, something they're doing for their continuation of their life. the problem is whether the various forms of buying and selling carried out are in accordance with the guidelines of Islamic ethics, because buying and selling prohibits the existence of physical ways and demands that every actor performs ways that are self-sufficient. As far as the author's observation, some Muslims have been able to apply the ethical values of buying and selling in their lives, but there are also some of them who have not been able to actualize these values. The contributing factors are lack of awareness and understanding of religion.Keywords:: Ethics of buying and Selling